Pembelajaran Jurnalistik Sebagai Media Pengembangan Kreativitas Menulis Santri Kelas Takhassus 3 Di Pondok Pesantren Tahfidz Daarul Qur'an Colomadu Tahun Pelajaran 2015/2016 - Hasanah, Sunnatul, Dra. Mahasri Shobahiya, M.Ag (2016)
This research is motivated by the problems associated with the low level of the creativity of learners in developing their writing ability, due to the lack of theory about writing learned and the limitations of time and occasion in writing. This is also caused by the lack of experience and appropriate learning in the world of writing in schools. This study has the formulation of the problem: Is journalism learning can develop creative writing from takhassus students at pesantren tahfidz daarul quran colomadu academic year 2015/2016? How the journalism learning can be a development medium of the writing creativity from takhassus student at pesantren tahfidz daarul quran colomadu academic year 2015/2016? The first aim of this study is to describe whether journalism learning can develop creative writing from takhassus students at pesantren tahfidz daarul quran colomadu academic year 2015/2016, and the Second is to describe How the journalism learning can be a development medium of the writing creativity from takhassus student at Pesantren Tahfidz Daarul Quran Colomadu academic year 2015/2016. The type of research is a field research with a qualitative approach. Collecting data is done by interviews, observation and documentation. Methods of data analysis in this research is descriptive analysis - qualitative; i.e. by exposing the existing data which is then associated with the existing data to be further conclusion. Based on the analysis, it was found that the learning of journalism can be a media in developing creative writing for learning journalism is learning individual skills in writing, because writing is a skill that must be trained and not natural skills, therefore, in developing the creativity of writing to go through the learning process in which there are several activities, events opener as initial activity, its core activities as a major activity in the learning experience and the final activity is a closing activity. Based on the data analysis, it is found that journalistic learning can be an appropriate media in the development of creative writing, through: (a) Learning in the classroom and outside the classroom that consists of a warm-up activity, core and closing activity. (b) Media development which include providing journalistic material feature, giving an image of a character, and a short film as adaptation of the events of everyday life. (c) During learning process in the classroom, the students are motivated to make a question related to a specific case study within its solution. (d) Creative writing development in which students are accustomed to write a short story. (e) Students are encouraged to write diary before bedtime. (d) Using the journalistic learning, Boarding School Tahfidz Daarul Qur'an Colomadu managed to overcome the problem of creative writing.